In Vivo Detection of External Apical Root Resorption Induced by Apical Periodontitis Using Periapical Radiography and Cone-Beam Computed Tomography - Stephanie Diaz Huamán; Maya Fernanda Manfrin Arnez; Fernanda Maria Machado Pereira Cabral de Oliveira; Andiara De Rossi; Léa Assed Bezerra Silva; Francisco Wanderley Garcia Paula-Silva (Association of Support to Oral Health Research (APESB), 2022)
Objective: To compare the accuracy of periapical radiography (PR) and cone-beam computed tomography (CBCT) for the detection of external apical root resorption (EARR) due to root canal contamination. Material and Methods: Dog's teeth with experimentally induced root resorption due to root canal contamination underwent or not root canal treatment (n=62). True positives (TP), false positives (FP), true negatives (TN), and false negatives (FN) in PR and CBCT diagnoses were determined using histopathologic findings as the gold standard. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy (TP + TN) in the diagnosis of EARR were calculated. Data were compared using chi-squared test (⍺=0.05). Results: EARR was detected in 35% of roots by PR, in 47% by CBCT, and in 50% of the roots by microscopy (p=0.03 PR versus microscopy; p=0.67 CBCT versusmicroscopy). Overall, CBCT produced more accurate diagnoses than PR (p=0.008). PR and CBCT allowed the identification of large resorption in 100% of the cases and showed the same accuracy. However, for small resorptions, PR showed an accuracy of 0.83, whereas CBCT showed an accuracy of 0.96 (p=0.003). Conclusion: Cone-beam computed tomography showed higher accuracy in detecting external apical root resorption of endodontic origin.